Using vignettes to explore policy tools for a self-driving transport future - Erik Almlöf (Transportation Research Interdisciplinary Perspectives, 2023)
Researchers struggle to create simple yet nuanced diagrams or short abstracts that are easily comprehendible by non-experts. Research articles may be our primary communication method, but they are generally difficult to understand, making them unsuitable for general communication.This paper investigates a rarely used method in transport research – vignettes – to convey research results and elicit implications for public planners. Historically, these vignettes have been designed using qualitative methods, e.g., the Delphi method or by researchers' review of trends. However, this paper uses two vignettes originating from quantitative results from a simulation model paper (Almlöf et al., 2022), investigating the impacts of self-driving technology. Rewriting the results into two short stories – vignettes – these stories then served as the starting point for semi-structured interviews and a workshop with six public officials in Stockholm, Sweden. The vignettes were used to understand what these results would mean to the participants and how they would combat potential problems connected to sustainability, given the vignettes. Finally, the interviews and the workshop were qualitatively analysed, and policy tools were identified that can steer the transport system towards societal goals.The vignettes were a powerful tool to help the participants envision a future with self-driving transport options and promote critical thinking regarding how each participant would be affected, given such a future. As such, vignettes should be further explored to help researchers investigate abstract subjects which participants may have difficulties understanding.